2003
DOI: 10.1177/153537020322800909
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes (db/db) Mutation-Induced Ovarian Involution: Progressive Hypercytolipidemia

Abstract: Ovarian atrophy and reproductive tract incompetence are recognized consequences of the progressive expression of the overt, diabetes-obesity syndrome (DOS) in C57BL/KsJ (db/db) mutant mice. The present studies evaluated the progressive changes in ovarian cytoarchitecture, endocrine expression, and reproductive tract cytolipidemic parameters that promote reproductive failure and ovarian involution during the pre-onset, initial, progressive, and chronic expression stages of the DOS. Paired littermate control (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(115 citation statements)
references
References 45 publications
1
114
0
Order By: Relevance
“…A progressive hyperglycemic-hyperinsulinemic condition in animal models of the diabetes-obesity syndrome was found to be associated with suppression of cyclic ovarian follicular recruitment patterns, anovulation, acyclicity, depressed ovarian steroid hormone synthesis and release, hypovascularization and tissue ischemia, enhanced follicular atresia, and premature tissue atrophy and involution (33,34). It was suggested that the extent of cellular involution observed in obesity and hyperglycemia could be related to glucotoxicity and the presence of a progressive cytolipotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…A progressive hyperglycemic-hyperinsulinemic condition in animal models of the diabetes-obesity syndrome was found to be associated with suppression of cyclic ovarian follicular recruitment patterns, anovulation, acyclicity, depressed ovarian steroid hormone synthesis and release, hypovascularization and tissue ischemia, enhanced follicular atresia, and premature tissue atrophy and involution (33,34). It was suggested that the extent of cellular involution observed in obesity and hyperglycemia could be related to glucotoxicity and the presence of a progressive cytolipotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that stringent glycemic control in diabetic patients improves menstrual cycles and fertility rates underlines the hypothesis that prolonged hyperglycemia and chronic complications of diabetes negatively affect ovarian reserve (37). Animal models have shown that ovulation was suppressed in hyperglycemic-hyperinsulinemic conditions, due to hypovascularization, follicular atresia, and eventually involution of ovaries, caused by glucotoxicity and the cytolipotoxic effect of obesity (38). It should, however, be stressed that due to the cross-sectional design of the current study, cause and effect could not be distinguished.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian atrophy and reproductive tract incompetence are recognized consequences of the progressive expression of the overt, diabetes-obesity syndrome (DOS) in diabetic mutant mice. In both humans and experimental models, utero-ovarian structural, functional, and metabolic parameters are altered in response to the progressive hyperglycemic-hyperinsulinemic systemic conditions that characterize noninsulin dependent (Type II) [10]. Diabetes can result in ovarian atrophy, suggesting that ovarian involution in these mutants is directly related to an impaired follicular ability to properly metabolize the elevated intracellular glucose concentrations that develop in the diabetic mice [13].…”
Section: Discussionmentioning
confidence: 99%
“…Garris and Garris demonstrated that enhanced lipid deposition and cellular metabolic indices promote a very nonhomeostatic, hyperlipogenic metabolic environment within all ovarian compartments of a diabetic mutant rat. The progressive deposition of enhanced interstitial and follicular lipid pools compromises the functional and structural characteristics of all ovarian cellular and tissue compartments, ultimately inducing a hypercytolipidemia, which contributes to premature tissue involution and ovarian failure [10]. Ishikawa et al [25] reported there were definite histopathological alterations such as mitochondrial abnormalities, dense bodies and lamellar structures at the nerve terminal innervating the dilator muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation